Home‐Based Family Intervention Increases Knowledge, Communication and Living Donation Rates: A Randomized Controlled Trial. Issue 8 (16th June 2014) - Ismail, S. Y.; Luchtenburg, A. E.; Timman, R.; Zuidema, W. C.; Boonstra, C.; Weimar, W.; Busschbach, J. J. V.; Massey, E. K.
<x xml:space="preserve">Abstract</x> Our aim was to develop and test an educational program to support well‐informed decision making among patients and their social network regarding living donor kidney transplantation (LDKT). One hundred sixty‐three patients who were unable to find a living donor were randomized to standard care or standard care plus home‐based education. In the education condition, patients and members of their social network participated in home‐based educational meetings and discussed renal replacement therapy options. Patients and invitees completed pre–post self‐report questionnaires measuring knowledge, risk perception, communication, self‐efficacy and subjective norm. LDKT activities were observed for 6 months postintervention. Patients in the experimental group showed significantly more improvements in knowledge (p < 0.001) and communication (p = 0.012) compared with the control group. The invitees showed pre–post increases in knowledge (p < 0.001), attitude toward discussing renal replacement therapies (p = 0.020), attitude toward donating a kidney (p = 0.023) and willingness to donate a kidney (p = 0.039) and a decrease in risk perception (p = 0.003). Finally, there were significantly more inquiries (29/39 vs. 13/41, p < 0.001), evaluations (25/39 vs. 7/41, p < 0.001) and actual LDKTs (17/39 vs. 4/41, p = 0.003) in the experimental group compared with the control group. Home‐based family education supports well‐informed decision making and promotes access to LDKT.